Facilitating learning and change in the daily lives of stroke survivors: A comparative analysis of municipal stroke rehabilitation services in Norway and Denmark - Arntzen, Cathrine; Moe, Siri; Aadal, Lena; Pallesen, Hanne (Cogent Medicine, 2019)
Purpose : This study describes and compare the ability of professionals working in municipality stroke rehabilitation services to facilitate learning and change in the daily living of stroke survivors in two regions: one in northern Norway, the other central Denmark. Materials and Methods : Semi-structured individual interviews were conducted with survivors 3 and 9 months after discharge from in-patient care. By contrast, field observations and focus group interviews were completed with professionals on multidisciplinary teams in the two regions. A sociocultural perspective on learning was applied during data analysis. Results : Altogether, the ability of municipal health services to facilitate learning and change for stroke survivors during the first year generally depended upon developing comprehensive integrated rehabilitation plans and ensuring access to coordinated, qualified multidisciplinary teams with professional knowledge and skills to support the survivors and their families during processes of adjustment, learning and change. However, Danish stroke survivors seemed positioned to be more active, proactive and empowered, and their processes of learning and change seemed more closely co-constructed with professional support. Conclusion : Findings reveal considerable differences in municipal stroke rehabilitation services in northern Norway and central Denmark and their ability to support stroke survivors in performing self-management.